Effect of different 3D-printing systems on the flexural strength of provisional fixed dental prostheses: a systematic review and network meta-analysis of in vitro studies - Ömer Yıldırım; Zeynep Yeşil; Ömer Hatipoğlu (BMC Oral Health)
Abstract Objectives The aim of this systematic review and network meta-analysis was to compare the flexural strength of provisional fixed dental prostheses (PFDPs) fabricated using different 3D printing technologies, including digital light processing (DLP), stereolithography (SLA), liquid crystal display (LCD), selective laser sintering (SLS), Digital Light Synthesis (DLS), and fused deposition modeling (FDM). Materials and methods A comprehensive literature search was conducted in databases including PubMed, Web of Science, Scopus, and Open Grey up to September 2024. Studies evaluating the flexural strength of PFDPs fabricated by 3D printing systems were included. A network meta-analysis was performed, using standardized mean differences (SMDs) and 95% confidence intervals (CIs) to assess the effects of each system on flexural strength. Results A total of 11 in vitro studies were included, with 9 studies contributing to the network meta-analysis. SLS (77.70%) and SLA (63.82%) systems ranked the highest in terms of flexural strength, while DLP ranked the lowest (23.40%). Significant differences were observed between SLS and multiple other systems, including DLP (-14.58, CI: -22.67 to -6.48), LCD (-14.65, CI: -25.54 to -3.59), FDM (-12.87, CI: -23.30 to -2.52), SLA (-11.41, CI: -18.74 to -4.01), and DLS (-10.89, CI: -21.23 to -0.67). Direct comparisons were limited, with DLP vs. SLA having the most data. Other comparisons were predominantly indirect. Conclusions SLS and SLA systems exhibited superior flexural strength compared to other systems. However, the limited number of direct comparisons and reliance on indirect evidence suggest that further research is necessary to confirm these findings.